THE LIFE QUALITY STUDY OF RURAL POPULATION IN THE KRASNOYARSK REGION BY THE METHOD OF COMPARATIVE SOCIAL INTEGRAL ASSESSMENT - Ljudmila Anatol’evna Yakimova (Science and Innovation Center Publishing House, 2020)
The population life quality is one of the most comprehensive and integrated concepts. In the scientific literature concerning research on the population life quality, there are many well-known methods that study the characteristics of the population life completeness and diversity. The purpose of this study is to develop a methodology for studying the population life quality, covering both quantitative (statistical) as well as qualitative (subjective) characteristics. Quantitative indicators such as the cost of living, the cost of the consumer basket, the level of officially registered unemployment, indicators of the natural population movement, the number of marriages and divorces for a certain period, etc., were taken from official statistical sources. To obtain subjective assessment characteristics of the life quality, we conducted a monitoring of rural population in the Krasnoyarsk region, in which at least 300 households were interviewed annually since 2006. The novelty of the scientific research is to develop a methodology for assessing the subjective perception of the population life quality, by calculating generalizing indicators that characterize the living and income standard of the rural population, the level of social tension, etc. This approach allows identifying a significant number of studied characteristics, which can be grouped according to various characteristics. As a result of the study, it turned out that quantitative indicators for the studied period indicate stability and some improvement in the population life quality of the Krasnoyarsk territory. The calculation of generalizing indicators characterizing the subjective assessment for the life quality of rural population showed that population is not satisfied with their housing situation. Two-thirds of respondents said that they need better housing conditions, which indicates tension in this area. It is also worth paying attention to the material well-being of rural population, increasing incomes and improving medical care. The use of the proposed methodology will help to competently develop management decisions in the field of state and municipal administration, in the formation of socio-economic strategy for the development of the region.